Love-Based Islamic Education: Assessing Teacher Readiness for Classroom Happiness and the Mitigation of Symbolic Violence in Madrasas - Muhamad Habib; Fathurohim Fathurohim; Ahmad Maliki; Imam Tobroni (IJoIS: Indonesian Journal of Islamic Studies, 2026)
The implementation of the Kurikulum Berbasis Cinta (KBC) marks a significant shift in Indonesian Islamic education, aiming to replace rigid pedagogical approaches with a framework centered on Mahabbah (love). Despite its theological appeal, the transition often faces hurdles regarding how educators internalize these values in daily interactions. The purpose of this study is to analyze teacher readiness in manifesting love-based education to create classroom happiness while mitigating subtle forms of symbolic violence in madrasas. This research utilized an explanatory sequential mixed-methods design, beginning with a quantitative survey of 100 Islamic Education teachers, followed by a qualitative phenomenological exploration involving in-depth interviews and classroom observations. The results reveal a notable Knowledge-Practice Gap, where teachers demonstrate high cognitive understanding (M=4.12) but remain at a moderate level of affective readiness (M=3.25). Furthermore, qualitative findings indicate that symbolic violence persists through subtle labeling and hidden administrative pressures, which hinder the full manifestation of classroom happiness. This study concludes that teacher readiness is the primary determinant of successful KBC implementation. Effective reduction of symbolic violence requires a shift from technical curriculum compliance to a deeper emotional and spiritual transformation of the educator.